A framework for estimating real-world bank valuations: a quantitative approach to identifying acquisition opportunities - Anderson, Dustin (My University, 2026)
The evaluation of bank acquisition targets often relies on tangible book value (TBV) as a primary valuation metric. However, TBV may not adequately reflect a bank’s true operational performance, profitability, or credit quality. This research aims to develop and apply a framework for estimating real-world bank valuations by adjusting TBV using performance-based metrics. The objective is to identify community banks that may be over- or undervalued relative to their intrinsic financial condition and, in doing so, enhance the acquisition screening process for banks, investors, and strategic buyers. This study utilizes FFIEC Call Report data collected from 4,299 U.S. banks over a three-year period (2022–2024), with historical data from 2016–2018 used to evaluate long-term loan growth trends. Financial information was obtained from a range of reporting schedules, including balance sheet data, income statements, loan quality, capital adequacy, and other relevant fields. Ten financial performance metrics were incorporated into a weighted scoring model to calculate an adjusted TBV and a valuation premium or discount for each institution. The metrics include return on equity, net interest margin, efficiency ratio, net charge-off rate, nonperforming loan ratio, leverage ratio, risk buffer ratio, loan-to-deposit ratio, loan compound annual growth rate, and loan concentration. A regression model was constructed to determine the degree to which these financial variables explain valuation premiums or discounts. The results show an adjusted R-squared value of 0.5064, confirming that over half of the variation in bank valuation premiums or discounts can be attributed to financial performance characteristics. Profitability, efficiency, and credit quality were found to be statistically significant drivers of valuation, while excess capital levels and generalized asset growth were not. Net interest margin showed the strongest positive relationship with valuation premium, while nonperforming loans and inefficiency were associated with valuation discounts. The findings indicate that traditional tangible book value is a poor standalone measure of bank value. By contrast, the adjusted TBV model introduced in this study provides a more accurate and meaningful assessment of intrinsic value and acquisition suitability. This framework offers a practical tool for narrowing the acquisition target universe and improving pre-due diligence decision-making by identifying undervalued institutions with strong financial fundamentals.
Keywords: Valuation; Bank; Profit; Efficiency; Credit; Acquisition